Patient-Specific 3D-Printed Miniplates for Free Flap Fixation at the Mandible: A Feasibility Study - Kreutzer, Kilian; Steffen, Claudius; Koerdt, Steffen; Doll, Christian; Ebker, Tobias; Nahles, Susanne; Flügge, Tabea; Heiland, Max; Beck-Broichsitter, Benedicta; Rendenbach, Carsten (Frontiers in Surgery, 2022)
Background: This study was conducted to evaluate the feasibility, clinical outcomes, and accuracy of patient-specific 3D-printed miniplates for mandible reconstruction with fibula free flaps. Methods: A feasibility study was conducted with 8 patients. Following virtual planning, patient-specific 1.0 mm titanium non-locking miniplates were produced via laser selective melting. 3D-printed cutting and drilling guides were used for segmental mandible resection and flap harvesting. Flap fixation was performed with two 4-hole miniplates and 2.0 mm non-locking screws (screw length 7 mm) for each intersegmental gap. Clinical follow-up was at least 6 months. Preoperative and postoperative CT/cone beam CT data were used for 3D accuracy analysis and evaluation of bone healing. Plate-related complications were monitored clinically. Results: Patient-specific miniplate fixation of all flaps was successfully conducted (4 mono-segmental, 4 dual-segmental) with high accuracy (3.64 ± 1.18 mm) between the virtual plan and postoperative result. No technical complications were encountered intraoperatively. Osseous union occurred in all intersegmental gaps (1 partial, 18 complete) after 10 ± 2 months. No material fracture, dislocation, or plate exposure was observed. Conclusions: Based on this pilot observational study including a limited number of patients, free flap fixation for mandibular reconstruction with patient-specific 3D-printed miniplates is feasible and associated with high accuracy, bone healing, and remote soft tissue complications.